Interplay of ribosomal DNA Loci in nucleolar dominance: dominant NORs are up-regulated by chromatin dynamics in the wheat-rye system - Silva, Manuela (2010)
Background: Chromatin organizational and topological plasticity, and its functions in gene expression regulation, have been strongly revealed by the analysis of nucleolar dominance in hybrids and polyploids where one parental set of ribosomal RNA (rDNA) genes that are clustered in nucleolar organizing regions (NORs), is rendered silent by epigenetic pathways and heterochromatization. However, information on the behaviour of dominant NORs is very sparse and needed for an integrative knowledge of differential gene transcription levels and chromatin specific domain interactions. Methodology/Principal Findings: Using molecular and cytological approaches in a wheat-rye addition line (wheat genome plus the rye nucleolar chromosome pair 1R), we investigated transcriptional activity and chromatin topology of the wheat dominant NORs in a nucleolar dominance situation. Herein we report dominant NORs up-regulation in the addition line through quantitative real-time PCR and silver-staining technique. Accompanying this modification in wheat rDNA trascription level, we also disclose that perinucleolar knobs of ribosomal chromatin are almost transcriptionally silent due to the residual detection of BrUTP incorporation in these domains, contrary to the marked labelling of intranucleolar condensed rDNA. Further, by comparative confocal analysis of nuclei probed to wheat and rye NORs, we found that in the wheat-rye addition line there is a significant decrease in the number of wheat-origin perinucleolar rDNA knobs, corresponding to a diminution of the rDNA heterochromatic fraction of the dominant (wheat) NORs. Conclusions/Significance: We demonstrate that inter-specific interactions leading to wheat-origin NOR dominance results not only on the silencing of rye origin NOR loci, but dominant NORs are alsomodified in their transcriptional activity and interphase organization. The results show a cross-talk between wheat and rye NORs, mediated by ribosomal chromatin dynamics, revealing a conceptual shift from differential amphiplasty to ‘mutual amphiplasty’ in the nucleolar dominance process.